If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) = 2(x + 1) Reorder the terms: 5(3 + x) = 2(x + 1) (3 * 5 + x * 5) = 2(x + 1) (15 + 5x) = 2(x + 1) Reorder the terms: 15 + 5x = 2(1 + x) 15 + 5x = (1 * 2 + x * 2) 15 + 5x = (2 + 2x) Solving 15 + 5x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 5x + -2x = 2 + 2x + -2x Combine like terms: 5x + -2x = 3x 15 + 3x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 3x = 2 + 0 15 + 3x = 2 Add '-15' to each side of the equation. 15 + -15 + 3x = 2 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 2 + -15 3x = 2 + -15 Combine like terms: 2 + -15 = -13 3x = -13 Divide each side by '3'. x = -4.333333333 Simplifying x = -4.333333333
| a-9a+75=135+2a | | -6z+8+4z=-3z+13 | | -8w+8-3w=2-6w+2 | | 11p+3p-15p=743 | | 8x-23=2x+2 | | n+(n+1)+(n+2)+(n+3)=-122 | | 7(x+5)-4=33-6x-2+13x | | 160+.40x=293.60 | | 4t-11=-1 | | 1.99s+(2.99*2s)+.15=40 | | 15-2(x+5)=25 | | 2+2+x=6 | | 2r-3=18 | | 11+2g=2g-(g-15) | | 3x+5=5y-8 | | w-1=5w+3w-8 | | 7p+11=3p | | 3+d=9-d | | 2(x+4)+(5x)=7(x+4)-5 | | 4c-3=17 | | 15-3.7m=12.84-2.5m | | -9(3y-4)=-531 | | 5(a-1)=2a+4(a-1) | | 5x+8(x+1)+3=11-3x | | 2(7h-3)=120 | | 4-4(x-3)=20 | | 8-5=11 | | -(1-x)=2(3x-1) | | 9y-6+y=-(y+5y) | | 7r+11r=725-7r | | 5(b+1)=5b+1 | | -25=7+4x |